Molecular mechanisms of anthracycline induced cardiotoxicity: Zebrafish come into play - Moossavi, Maryam; Lu, Xiaoguang; Herrmann, Joerg; Xu, Xiaolei (Frontiers in Cardiovascular Medicine, 2023)
Anthracyclines are among the most potent chemotherapeutics; however, cardiotoxicity significantly restricts their use. Indeed, anthracycline-induced cardiotoxicity (AIC) fares among the worst types of cardiomyopathy, and may only slowly and partially respond to standard heart failure therapies including β-blockers and ACE inhibitors. No therapy specifically designed to treat anthracycline cardiomyopathy at present, and neither is it known if any such strategy could be developed. To address this gap and to elucidate the molecular basis of AIC with a therapeutic goal in mind, zebrafish has been introduced as an in vivo vertebrate model about a decade ago. Here, we first review our current understanding of the basic molecular and biochemical mechanisms of AIC, and then the contribution of zebrafish to the AIC field. We summarize the generation of embryonic zebrafish AIC models (eAIC) and their use for chemical screening and assessment of genetic modifiers, and then the generation of adult zebrafish AIC models (aAIC) and their use for discovering genetic modifiers via forward mutagenesis screening, deciphering spatial-temporal-specific mechanisms of modifier genes, and prioritizing therapeutic compounds via chemical genetic tools. Several therapeutic target genes and related therapies have emerged, including a RA-based therapy for the early phase of AIC and an autophagy-based therapy that, for the first time, is able to reverse cardiac dysfunction in the late phase of AIC. We conclude that zebrafish is becoming an important in vivo model that would accelerate both mechanistic studies and therapeutic development of AIC.